System for Safe Smart Lab Administration and Control - Sayyad-Modi, Shabina; Rajendra Chavan, Vaishnavi; Sanjay Kadam, Rutuja; Shankar Mane, Nikit; Pramod Jadhav, Aditya; Doshi, Ketan Mahesh (International Journal of Computer Sciences and Engineering, 2023)
In today`s age of digitization and automation, the life of humans is increasingly easier because virtually everything has been reprogrammed and replaces old manually generated procedures. Today`s people make use of the Internet to this day in their everyday lives, and that leaves them unable to function without it. The Internet of Things offers a platform that allows devices to connect, detect and remote control objects on the network infrastructure. Lab automation is a major focus of our project. Currently, none of the colleges` and schools` labs are automated. Wireless systems, can be a great asset for automation systems. The presence of students in the lab, the lab`s temperature, and its humidity can be checked automatically. Automated labs means monitoring entry of students and person’s entering in the labs and providing security to labs when there is off period of institute it helps to security when anyone trying to enter in the labs. Software provides platform to students and teacher to meet online at one place. The system extends the home robotization technology to the council laboratories, and hence to produce a smart laboratory.